Quality Evaluation of Kiwi Juice Coagulated Mozzarella Cheese - Karki, Anubodh; Ojha, Pravin (Journal of Food Science and Technology Nepal, 2018)
Standardized milk having casein: fat ratio 0.92 was used and the processes were optimized for the manufacture of cheeses. The samples were analyzed for physico-chemical properties (moisture, total solid, fat, protein, ash, calcium, fat retention, protein retention, yield) and functional properties such as meltability, stretchability, baking quality and shreddability were also analyzed. Significant differences (p<0.05) were found in calcium content of the cheese, color and overall sensory properties. Stretchability and shreddability in relation to functional properties were also found to be significantly different. The yield for mozzarella cheese made using rennet was higher than that of cheese made using kiwi juice as milk coagulant and also it was superior in terms of overall functional properties. It was deemed that a good quality mozzarella cheese with variant characteristics can be prepared by using kiwi juice as milk coagulant.